Dampak Rasio Keuangan terhadap Kebijakan Deviden - Dwi Purwanti; Peni Sawitri (BISMA (Bisnis dan Manajemen), 2018)
Dividends are important for companies because it is associated with an appropriate allocation of income of the company's growth and prosperity so that shareholders can be assured. This study aims to analyze the effect on financial ratios, dividend payout ratio by five independent variables (Earning Per Share, Debt To Equity Ratio, Price Book Value, Return On Investment, and Total Asset Turn Over). Sampling method used was purposive random sampling. Analysis tool used is multiple linear regression and hypothesis testing using t test and f. Sample who is 14 companies listed in Indonesia Stock Exchange during the five year period 2005 to 2009. The results showed that the Debt To Equity Ratio (DER), Return On Investment (ROI) and Total Asset Turn Over (tattoo) effect on cash dividends in the companies listed in Indonesia Stock Exchange, while Earning Per Share (EPS) and Price Book Value (PBV) has no effect on Cash Devidend. While jointly (simultaneously), the fifth variable is Earnings Per Share, Debt to Equity Ratio, Price Book Value, Return On Investment, Total Assets Cash Turn Over striving affect dividend. Allows no variables that have a dominant influence on Devidend Payout Ratio (DPR). This is because the global economic crisis